2007
DOI: 10.1037/0735-7044.121.6.1306
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gestational ethanol exposure on voluntary ethanol intake in early postnatal and adult rats.

Abstract: Clinical and epidemiological studies provide strong data for a relationship between prenatal ethanol exposure and the risk for abuse in adolescent and young adult humans. However, drugacceptance results in response to fetal exposure have differed by study, age at evaluation, and experimental animal. In the present study, the authors tested whether voluntary ethanol intake was enhanced in both the infantile and adult rat (15 and 90 days of age, respectively), as a consequence of chronic fetal drug experience. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 88 publications
9
63
0
3
Order By: Relevance
“…1 also demonstrated that the increased acceptability of ethanol and QHCl to P30 animals was absent in P90 adult animals. This finding agrees with previous observations that the olfactory and ethanol intake effects of fetal exposure, while present in infant (16,17) and adolescent rats (4,5,18,19), ameliorate by adulthood (16,17). Even so, the conjunction of these data with the clinical literature (2, 3) point to the importance of adolescence as a critical transition period for perpetuating mechanisms that contribute to the development of alcoholism.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…1 also demonstrated that the increased acceptability of ethanol and QHCl to P30 animals was absent in P90 adult animals. This finding agrees with previous observations that the olfactory and ethanol intake effects of fetal exposure, while present in infant (16,17) and adolescent rats (4,5,18,19), ameliorate by adulthood (16,17). Even so, the conjunction of these data with the clinical literature (2, 3) point to the importance of adolescence as a critical transition period for perpetuating mechanisms that contribute to the development of alcoholism.…”
Section: Discussionsupporting
confidence: 91%
“…We previously found that (i) infant rats exposed to ethanol throughout gestation displayed a tuned neural and behavioral olfactory response that was specific to ethanol odor (16) and (ii) that this observation was paralleled by enhanced ethanol intake (17). These observations raised the clinically relevant possibility that the effects of fetal ethanol exposure on olfactory function may be an important contributor to an enhanced postnatal avidity for the drug.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations